صفات الشخصية العربية في المصادر المسمارية: دراسة تاريخية - السعدون، عبدالغني غالي فارس (جامعة البصرة ومركز البحث وتطوير الموارد البشرية رماح, 2020)
عنى البحث بدراسة صفات الشخصية العربية في المصادر المسمارية من وجهة نظر تاريخية. وقد قسمناه على محورين رئيسين، تناول الأول منهما المصادر المسمارية التي ذكرت العرب. أما المحور الثاني فتطرق لصفات الشخصية العربية. ومن مجمل هذه الدراسة اتضح أن هذه المصادر عبارة عن نصوص ونقوش آشورية وبابلية وأخمينية، تعود إلى المدة الواقعة بين منتصف القرن التاسع قبل الميلاد والنصف الثاني من القرن السادس قبل الميلاد، وأن العرب الذين ذكروا فيها هم بالدرجة الأساس سكان شمال غرب شبه الجزيرة العربية من بدو وحضر. كذلك اتضح أن شخصية أولئك العرب امتازت بجملة من الصفات مثل الإباء وعزة النفس والمروءة، فضلا عن الحكمة والدهاء السياسي والتدين الشديد. وقد تم التعرف إلى صفاتهم تلك من خلال ما ذكرته المصادر المسمارية عن علاقتهم بكل من الآشوريين والبابليين والفرس الاخمينيين. ويمكن القول إن هذه الصفات كانت نتيجة لطبيعة بيئة منطقتهم، وللأعراف والتقاليد المتأصلة في نفوسهم.
of the research is to study the characteristics of the Arab personality through cuneiform sources from a historical point of view. We divided it into two main axes, the first of which dealt with the cuneiform sources that mentioned the Arabs. As for the second and last axis, it deals with the characteristics of the Arab character. From the entirety of this study, it became clear that these sources are Assyrian, Babylonian and Achaemenes texts, inscriptions and cartoons, dating back to the period between the middle of the ninth century B.C and the second half of the sixth century B.C., and that the Arabs who mentioned them are mainly residents of northwestern Arabia Those who appeared and attended. also that the personality of these Arabs was distinguished by a number of attributes, such as fatherhood, self-esteem, and virility, as well as wisdom, political savvy and extreme religiousness. Their characteristics were identified through what the Cuneiform sources mentioned about their relationship with both the Assyrians, the Babylonians, and the Achaemenes Persians. It can be said that these characteristics were a result of the nature of their region's environment, and the customs and traditions inherent in their soul
Keywords: السمات الشخصية -- الهوية العربية -- المصادر التاريخية -- الحضارة المسمارية